Informed consent: ethical and legal consideration / Suria Fadhillah Md Pauzi and Nadia Omar - Md Pauzi, Suria Fadhillah; Omar, Nadia (2004)
In health care, there are a number of pertinent issues, which have no "right or wrong" answers. These are in the "grey areas" of a medical ethic where religious belief and cultural background plays prominent role in deciding which is the best answer which might not be accepted as unchallengeable right. Growing public awareness with regard to advances in medical science has increased the need for patients to be given more information before they submit to any medical treatment. Informed consent, thus, has been of current interest to the community as patients claim greater participation in medical decision-making. In allowing this to occur, the law has much difficulty in balancing the rights of the patient on one hand, and the rights of the doctor, on the other. We believe that much of the negative reaction to informed consent sterns from some fundamental misunderstandings about what informed consent requires. How much must the patient be told of the risks involved in a recommended operation or course of treatment? By what standard is the medical practitioner's duty of disclosure judged and what are the legal consequences attendants upon failure to obtain informed consent? This article endeavors to provide some answers to these questions in the light of the approach taken by the courts in various countries.